PERTANGGUNG JAWABAN IBU PENGIDAP GANGGUAN JIWA PASCA NIFAS (POSTPARTUM DEPRESSION) YANG MELAKUKAN TINDAK PIDANA KEPADA ANAKNYA - Haifa, Haifa; Syaufi, Ahmad (Universitas Muara Bungo, 2025)
This study aims to determine the legal provisions regarding mothers with postpartum depression who commit criminal acts against their children, as well as the ideal concept of provisions regarding mothers with postpartum depression who commit criminal acts against their children based on the principle of benefit. This research is a normative legal research that is descriptive analytical with a case approach, conceptual approach, and legislative approach. The types of materials used are primary and secondary legal materials. Based on this research, the results obtained show that the ability to be responsible is closely related to a person's mental state when committing an act. A person who is proven to have a mental disorder cannot be punished according to the provisions of Article 44 paragraph (1) of the Criminal Code. Mothers who experience postpartum depression in criminal law provisions can still be charged with child abuse or even murder as regulated in the legislation. The state has been legally present to provide assistance to both mothers and their children, through Law No. 4 of 2024, Article 4 paragraph (1) which talks about the rights of every mother, one of which is to receive consultation services, psychological services, and/or religious guidance. However, this is only a preventive or preventive movement, the aim of which is to prevent mothers from suffering from mental disorders. The ideal concept regarding mothers with postpartum depression who commit crimes against their children based on the principle of benefit is that there must be regulations that order the state to provide psychological assistance to mothers. That way, the state will also provide legal benefits to the mother, as well as to the environment where the mother will return after undergoing the legal process.Key words: Accountability, Postpartum Depression, Criminal Acts